Transforming Enterprise Systems through Event-Driven Architecture: Implementation, Benefits, and Future Trends - Amlan Ghosh, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Event-driven cloud architectures have fundamentally transformed how organizations design, deploy, and scale their digital infrastructure across various industries. This comprehensive technical article explores the evolution and impact of event-driven architecture (EDA) in modern cloud computing, examining its core components, implementation patterns, and industry-specific applications. Through analyzing real-world use cases spanning financial services, healthcare, retail, and manufacturing sectors, it demonstrates how EDA enables organizations to build more responsive, scalable, and efficient systems. The article addresses critical challenges in implementing event-driven systems, including consistency, monitoring, and security considerations, while providing practical solutions and best practices. Furthermore, this article investigates emerging trends in event-driven architectures, particularly their integration with artificial intelligence, machine learning, and serverless computing paradigms. This article suggests that organizations adopting EDA can achieve significant improvements in operational agility, customer experience, and resource utilization, positioning them for success in an increasingly dynamic digital landscape.
Keywords: Event-Driven Architecture (EDA); Cloud Computing; Microservices; Real-time Processing; Digital Transformation